EDUCATION BEYOND THE LABOR MARKET - Amanda da Silva Menger; Vera Lúcia Chacon Valença (Editora da Universidade de Santa Cruz do Sul, 2012)
The article "Education beyond the labor market" is proposed to make a reflection of current education in Brazil. The starting point is the observation of the emphasis placed by government actions to an aspect of education: preparation for work. Furthermore, the article presents a retrospective of this aspect of education throughout the history of education.